2017
DOI: 10.1038/srep43227
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of validation and application on various cardiovascular disease mortality risk prediction models in Chinese rural population

Abstract: This research aims to assess application of different cardiovascular disease (CVD) mortality risk prediction models in Chinese rural population. Data was collected from a 6-year follow-up survey in rural area of Henan Province, China. 10338 participants aged 40 to 65 years were included. Baseline study was conducted between 2007 and 2008, and followed up from 2013 to 2014. Seven models: general Framingham risk score (general-FRS), simplified-FRS, Systematic Coronary Risk Evaluation for high (SCORE-high), SCORE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…These findings may be due to the fact the FRS model was developed from individuals of Caucasian ethnicity. Validation and recalibration should be conducted before this risk assessment tool can be applied in other populations [23]. Existing models mostly included hypertension predictors based on the FRS model [13-20], which was easily available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings may be due to the fact the FRS model was developed from individuals of Caucasian ethnicity. Validation and recalibration should be conducted before this risk assessment tool can be applied in other populations [23]. Existing models mostly included hypertension predictors based on the FRS model [13-20], which was easily available.…”
Section: Discussionmentioning
confidence: 99%
“…This survey is a 6-year population-based prospective cohort study in the rural areas of Henan Province, China (Figure S1 in Online Supplementary Document s howed the position where data was collected). Details of the study design and methods have been described and reported previously [22,23]. Briefly, the baseline survey was conducted from July to August of 2007 and of 2008.…”
Section: Methodsmentioning
confidence: 99%
“…The definition of CVD in the Hong Kong cohort was similar to ours, but the sudden death for unknown reason was also included in the outcome. Previous validation of risk scores developed in populations of European ancestry among Chinese populations have only shown moderate performance, even after recalibration leading to recommendations that ethnic-specific risk scores are developed [ 32 33 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, all older patients with hypertension received antihypertensive drugs according to Chinese guidelines for the management of hypertension during follow-up ( Sun et al, 2017 ). In this study, patients with hypertension were divided into two categories: treated but with uncontrolled hypertension and hypertension controlled with medication.…”
Section: Methodsmentioning
confidence: 99%